(untitled) (Journal of Enam Medical College, 2014)
Colon perforation is an uncommon event usually caused by malignancy, diverticular disease, amoebic colitis, steroid therapy, trauma and ulcerative colitis, but stercoral perforation is very rare. Severe chronic constipation is considered to be the main causative factor in development of stercoral perforation of colon. Sometimes it can also produce catastrophic complications like colonic obstruction, faecal peritonitis and septicaemia. We report a rare case of sigmoid colonic perforation with faecal peritonitis and pneumoperitonium due to faecaloma which was diagnosed after exploratory laparotomy. DOI: http://dx.doi.org/10.3329/jemc.v4i3.20959 J Enam Med Col 2014; 4(3): 188-190